Hypolipidaemic Potentials of Vernonia amygdalina (Bitter Leaf) in male albino rats fed high-sucrose diet - Olooto Wasiu Eniola; Ogunkoya Oluwaseun Odunayo; Alabi Akinyinka Oyedolapo; Oyinloye Elijah Oladapo (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2017)
Background: Increasing prevalence of obesity, overweight and metabolic syndrome secondary to excessive consumption of a high-sucrose and high-fat diet is a major global health problem. Objective: This study was meant to determine the hypolipidaemic potentials of phytochemicals present inVernonia amygdalina(Bitter leaf) in obese rats. Method: Thirty-two (6 weeks old, weighing 150-160g) male Wistar rats, were randomly selected and grouped into four: with eight rats in each group. The rats in the control group were fed normal rat chow and water while the three experimental groups were fed the various compounded diets and water ad libitum. At the end of 12th week, the animals fasted overnight, and Oral Glucose Tolerance Test (OGTT) was performed in some while others were anaesthetized using diethyl ether. Fasting plasma, liver tissue lipid and lipoprotein levels were determined, and LDL-C was calculated. Result: Rapid weight gain (89.9%) was recorded in rats fed High Sucrose Diet [HSD] when compared with the control group (55.3%) without significant differences in the liver weight. The mean plasma glucose, triglyceride, total cholesterol and LDL-C levels were significantly higher (p = 0.000, p = 0.010, p = 0.000 and p = 0.002 respectively) while mean plasma HDL-C was significantly lower (p = 0.043) in rats fed HSD when compared with rats fed normal rat chow. A significantly lower plasma lipid and higher liver tissue HDL-C (p = 0.03) were observed in the Vernonia amygdalina-treated rats. Conclusion: HSD induces hepatic steatosis and the related biochemical changes while dietary Vernonia amygdalina ameliorates the biochemical changes in hepatic steatosis in rats.